ANALISIS PENGARUH E-WOM, BRAND IMAGE,DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA TRANSPORTASI DI BALI - Pande Ketut Ribek; I Kadek Dwita Cahyadi Wiguna (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
Companies will grow and gain a competitive advantage by providing the best quality service, ensuring customer satisfaction and a desire to use the company's services. This study aims to determine and analyze the influence of word of mouth, brand image, and service quality on the decision to use transportation services in Bali. A purposive sampling technique was used to select 80 respondents, representing transportation customers in Denpasar. Data were collected using a Likert-scale questionnaire and processed using the Statistical Program for Social Science (SPSS). The results demonstrate that word of mouth, brand image, and service quality have a positive and significant influence on the decision to use transportation services in Denpasar.